Hologram quantitative structure–activity relationship and topomer comparative molecular-field analysis to predict the affinities of azo dyes for cellulose fibers. (June 2018) - Yu, Shuling; Zhou, Qiaoqiao; Zhang, Xuliang; Jia, Shuxin; Gan, Ying; Zhang, Yahong; Shi, Jiahua; Yuan, Jintao
Abstract: A hologram quantitative structure–activity relationship (HQSAR) and topomer comparative molecular-field analysis (CoMFA) were performed on 51 molecules that belong to the azo dyes to determine their affinities to cellulose fiber. The best HQSAR model was obtained by using atoms. Hydrogen atoms as a fragment distinction and a fragment size of 3–6 showed a leave-one-out cross-validated correlation coefficient ( q 2 LOO ) of 0.849 and a non-cross-validated correlation coefficient ( r 2 ) of 0.927. The best topomer CoMFA model with steric and electrostatic field parameters based on three fragments gave satisfactory results ( q 2 LOO  = 0.821; r 2  = 0.934). External predictions were made on a test set and compared with previously reported models. Topomer CoMFA steric, electrostatic, and HQSAR atomic contribution maps were generated to analyze the structural features of this data set that govern their affinity potency. Highlights: Fifty-one azo dyes were studied by the HQSAR and topomer CoMFA methods. HQSAR and topomer CoMFA models were validated by a test set and external parameters. The obtained models were compared with reported models. The graphically results of the HQSAR and topomer CoMFA models were analyzed for designing new dyes.